FAIR-IMPACT National Roadshow in Greece - Implementing FAIR principles: Tools, Infrastructure and Guidelines and the Greek Horizon - Kalaitzi, Vasso; Zamani, Themis; Koumantaros, Kostas; Simaioforodis, Zisis; Karaiskou, Theodora; Psomopoulos, Fotis; Papadopoulou, Elli; Kokkinaki, Alexandra; Mystakopoulos, Fotis; Pittonet Gaiarin, Sara (Zenodo (CERN European Organization for Nuclear Research), 2024)
The FAIR National Roadshow series visited Greece on the 18th of November 2024. This virtual event, hosted by FAIR-IMPACT, was a collaborative effort co-organised with GRNET, OPERAS, OpenAIRE, the Athena Research Center, HEAL-Link, and the University Library of Patras. The program highlighted national-level initiatives in Greece, aiming to bridge the gap between research institutes and universities on Open Science and FAIR practices. Find more details on the event page here.